Application of a Novel Common-Iliac-Artery Skirt Technology (CST) in Treating Challenge Aorto-Iliac or Isolated Iliac Artery Aneurysms - Wang, Lunchang; Shu, Chang; Li, Quanming; Li, Ming; He, Hao; Li, Xin; Shi, Yin; Qiu, Jian; Wang, Tun; Yang, Chenzi; Wang, Mo; Li, Jiehua; et al. (Frontiers in Cardiovascular Medicine, 2021)
Purpose: To report a novel common-iliac-artery skirt technology (CST) in treating challenge iliac artery aneurysms. Methods: When required healthy landing zone of common iliac artery (CIA) is not available, CST is a strategy to exclude the internal iliac artery (IIA) and prevent IIA reflux without need of embolization. Patients received endovascular aneurysm repair (EVAR) in our center from 2014 to 2020 were retrospectively screened, and patients treated with CST or with IIA embolization (IIAE) were enrolled. Results: After retrospective screen of 524 EVAR patients, 39 CST patients, 26 IIAE patients, and 7 CST+IIAE patients were enrolled in this study. CST group suggested to have more aged, hyperlipemia and smoking patients than IIAE group. Two groups had comparable maximal diameter of abdominal aorta (AA), CIA, EIA, but larger diameter of IIA (CST 19.82±2.281 vs IIAE 27.82±3.401, p=0.048), and CIA bifurcation (CST 25.01±1.316 vs IIAE 29.76±2.775, p=0.087) was found in IIAE group. Anatomy of 79.5% of CST patients and 92.3% of IIAE patients (p=0.293) were not suitable for potential use of iliac branch device. CST group had significant shorter surgery time (CST 97.42±3.891 vs IIAE 141.0±8.010, p<0.001), shorter hospital stay (CST 15.35±0.873 vs IIAE 19.32±1.067, p=0.009), lower in-hospital (CST 0%(0/39) vs IIAE 11.5%(3/26), p=0.059) and 1-year follow-up stent related MAEs (CST 6.7%(2/30) vs IIAE 28.6%(6/21), p=0.052), but comparable mortality and stent related MAEs for all-cohort follow-up analysis comparing to IIAE group. In our study, a lower in-hospital buttock claudication (BC) rate for CST (CST 20.5% vs IIAE 46.2%, p=0.053), and a comparable erectile dysfunction (ED) rate (CST 10.3% vs IIAE 23.1%, p=0.352) was found between CST and IIAE groups. After one year, both groups had about one third relief of BC symptoms (CST 33.3%(4/12) vs IIAE 30.7%(4/13), p=1.000). Subgroup analysis of 14 patents concomitant with IIA aneurysm in CST group and the 7 CST+IIAE patients were carried out and no difference was found in mortality, stent MAEs, sac dilation or reintervetion rate. Last, illustration of 7 typical CST cases was presented. Conclusion: In selected cases, the CST is a safe, feasible-and-effective choose in treating challenge iliac artery aneurysms and preventing IIA endoleak.